Safety and Efficacy of Prosopis juliflora Leaf Extract as a Potential Treatment against Visceral Leishmaniasis in Balb/c Mice - Muendo Charity Mutile (Tehran University of Medical Sciences, 2021)
Background: Visceral Leishmaniasis caused by Leishmania donovani is a major health problem in the tropics and sub-tropic regions where it is endemic. We aimed in testing the leishmanicidal activity and toxicity of Prosopis juliflora leaf extract in BALB/c mice and in vitro test systems respectively.